Meningococcal C conjugate age-dependant long-term loss of effectiveness. Issue 19 (5th May 2015) - Garrido-Estepa, M.; Nuñez, O.G.; León-Gómez, I.; Cano, R.; Herruzo, R.
Abstract Introduction Although different epidemiological studies have assessed meningococcal C conjugate vaccine effectiveness within 1 and >1 year since vaccination, none of them evaluated long-term effectiveness. In order to assess if epidemiological data correlates with the findings described in seroprevalence studies we evaluated long-term vaccine effectiveness over time, up to 10 years since vaccination. Methods Cases targeted by vaccination programs and notified to the Spanish Surveillance System between 2001 and 2013 were included in the study. Vaccine effectiveness was estimated using the screening method. Relationship between vaccine effectiveness and time since vaccination was explored using point estimates, simple logistic regression or restricted cubic splines logistic regression model for all and for those vaccinated at <1, 1–11 and at 12–19 years of age. Results From 345 confirmed cases reported in the period and targeted by vaccination programs, 125 (36.23%) were vaccine failures. Proportion of vaccine failures decreased with age of vaccination: 63.97% at <1 year; 36.84% at 1–11 years; and 3.88% at 12–19 years. Using the best model for each group, vaccine effectiveness decreased from 99.12% to 90.85% (%change = −8.3%) for all; from 99.04% to 48.60% (%change = −50.9%) for those vaccinated at <1 years and from 99.45% to 90.18% (%change = −9.3%) for those vaccinated at 1–11 years after 10 years since vaccination. For those vaccinated at 12–19 years no changes were observed in vaccine effectiveness after 10 years (p = 0.968). Conclusions After 10 years, vaccine effectiveness decreased by 50% in those vaccinated at <1 year, while those vaccinated with one dose at 12–19 years showed no changes. Vaccine failures occurred early after vaccination and more frequently in those vaccinated at younger ages. Vaccination at ≥12 years seems to be related to a low number of vaccine failures and a higher and endurable protection over time.